Neuropsychopharmacology of a therapeutically used Andrographis paniculata extract: A preclinical study - Thakur A.K.; Chatterjee S.S.; Kumar V. (My University, 2025)
Andrographis paniculata (Burm. F.) Wall. Ex Nees (Acanthaceae) also called as Kalmegh, or "King of Bitters". In Ayurveda, Andrographis paniculata is classified as a Rasayana herb. More than 50 % of the poly-herbal formulations commercialized in India for treatment of liver function disorders contain Andrographis paniculata. Pilot study and general neuropharmacological screening were conducted with analytically standardized Andrographis paniculata extract (AP), to evaluate its therapeutic potential for mental health problems. A battery of rodent behavioral models developed in our laboratory was used for characterizing brain function modulating activities. Daily oral administrations of even very high doses (800 mg/kg) of the extract were well tolerated by laboratory rodents without any apparent behavioral alterations. A single oral dose of the extract (AP 25 to 800 mg/kg) was inactive in mice stress-induced hyperthermia, and apomorphine induced cage-climbing tests in rats. However, dose and duration of treatment dependent efficacy of the extract after its daily doses up to 200 mg/kg/day for 10 days was observed in both the tests. Moreover, dose dependent effects of the extract in suppressing locomotion, potentiating pentobarbital sleep, and antagonizing pentylenetetrazole or maximal electroshock triggered seizures were also apparent after its 10 daily doses up to 200 mg/kg/day. Anxiolytics and antidepressants-like activity of AP treatment was also apparent in rats after 10 daily doses. Therefore, prolonged daily oral intake of Andrographis paniculata extract gradually suppresses central sensitivity to acute stressful stimuli, and eventually down regulates central dopaminergic receptors. Benzodiazepines like anxiolytic and seizure suppressing activities of the extract can be expected after its daily intake. © 2013 Institute of Korean Medicine, Kyung Hee University.